1966
DOI: 10.1161/01.cir.34.2.226
|View full text |Cite
|
Sign up to set email alerts
|

Studies in Man on the Relationship of Adrenergic Correlates to Pressor Responsivity

Abstract: 226 at RUTGERS UNIVERSITY on April 5, 2015 http://circ.ahajournals.org/ Downloaded from III, the catecholamines were separated from duplicate aliquots of urine on British Drug House 227 at RUTGERS UNIVERSITY on April 5, 2015 http://circ.ahajournals.org/ Downloaded from of sensory stimulation upon the blood pressure.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
12
0

Year Published

1968
1968
1978
1978

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(13 citation statements)
references
References 27 publications
1
12
0
Order By: Relevance
“…In our previous study, it was shown that these biochemical measurements did not correlate with the cardiovascular response, but rather seemed to relate to the individual's concept or perception of the stimulus. 3 Other investigators have shown similar variation in steroid and FFA levels which relate to such aspects of the stimulus or situation as its "novelty." 11 '-14 Although the relationship of the biochemical measurements to the meaning of the stimulus is not established in the present study, the former again fail to correlate with the cardiovascular responses.…”
Section: Discussionmentioning
confidence: 94%
See 3 more Smart Citations
“…In our previous study, it was shown that these biochemical measurements did not correlate with the cardiovascular response, but rather seemed to relate to the individual's concept or perception of the stimulus. 3 Other investigators have shown similar variation in steroid and FFA levels which relate to such aspects of the stimulus or situation as its "novelty." 11 '-14 Although the relationship of the biochemical measurements to the meaning of the stimulus is not established in the present study, the former again fail to correlate with the cardiovascular responses.…”
Section: Discussionmentioning
confidence: 94%
“…Next, apparatus was attached for recording blood pressure and pulse rate by indirect techniques, as previously described. 3 The subject then rested for 15 min., following which two stimuli were administered, with another 15-min. rest period between them.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…21 The stimuli were administered at 10 to 15 minute intervals after an initial rest period of at least 15 minutes. The sequence of administration of the stimuli was varied randomly from patient to patient and from one testing session to the other within the same patient.…”
Section: Methodsmentioning
confidence: 99%